2019
DOI: 10.1007/s00018-019-03025-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional subgroups among genetically identified cholinergic neurons in the pedunculopontine nucleus

Abstract: The pedunculopontine nucleus (PPN) is a part of the reticular activating system which is composed of cholinergic, glutamatergic and GABAergic neurons. Early electrophysiological studies characterized and grouped PPN neurons based on certain functional properties (i.e., the presence or absence of the A-current, spike latency, and low threshold spikes). Although other electrophysiological characteristics of these neurons were also described (as high threshold membrane potential oscillations, great differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
3
4
0
Order By: Relevance
“…We found that different projection patterns of PTCNs in the PPN and LDT had rich dendrites ( Figure 3B ). Consistent with previous studies (Baksa et al, 2019), we divided the dendrites with bipolar and multipolar dendritic trees according to the distribution of longer dendrites ( Figure 3B ) and found a few of them had bipolar dendritic trees while most were multipolar (Figure 3—figure supplement 1). Then we analyzed the spatial distribution of dendritic branches with the Sholl analysis ( Figure 3C ).…”
Section: Resultssupporting
confidence: 86%
“…We found that different projection patterns of PTCNs in the PPN and LDT had rich dendrites ( Figure 3B ). Consistent with previous studies (Baksa et al, 2019), we divided the dendrites with bipolar and multipolar dendritic trees according to the distribution of longer dendrites ( Figure 3B ) and found a few of them had bipolar dendritic trees while most were multipolar (Figure 3—figure supplement 1). Then we analyzed the spatial distribution of dendritic branches with the Sholl analysis ( Figure 3C ).…”
Section: Resultssupporting
confidence: 86%
“…We observed that KCNQ4-possessing cholinergic neurons are rather located in the caudal PPN. This observation strengthens the view that PPN neurons are far from uniform, but have several functional subgroups in terms of membrane properties ( Baksa et al, 2019 ). Furthermore, the rostral PPN (known as pars dissipata) differs from the caudal part (pars compacta) in efferent connectivity, as rostrally located cholinergic neurons project to the dorsolateral striatum and substantia nigra pars compacta, whereas the caudally located ones project to the VTA and the dorsomedial striatum ( Martinez-Gonzalez et al, 2011 ).…”
Section: Discussionsupporting
confidence: 88%
“…This is based on the neurons having low threshold spiking, a transient outward potassium current (known as A-current), both of these properties, or none. In addition, it has also been found that cells with A-current can be either early or late firing (Baksa et al, 2019). The diversity in functional properties of cholinergic neurons is important as they are tonically firing and thus different characteristics could lead to different ACh release patterns, altering circuit activity.…”
Section: Genetic Diversity May Lead To Functional Subgroups In Cholinmentioning
confidence: 99%